Soroepidemiologia de neospora caninum em caprinos (Capra hircus) do Estado da Paraíba - Braz., Beatriz Maria de Almeida (2015)
The neosporosis is recognized as a protozoan infection caused by Neospora caninum. It is primarily associated with cases of abortion and neonatal mortality in cattle. In Brazil, several studies focusing on this agent have been developed, however in the Northeast there are few studies about this disease and its impact on goat herds. The aim of this study was to investigate the prevalence of anti N. caninum antibodies in goats from Paraíba state. It was collected 406 goat blood samples (35 males and 371 females) from 8 different farms belonging to rural areas from Paraíba state. A total of 106/406 (26.11%; 95% CI 21.96 to 30.72%) were seropositive for indirect immunofluorescence antibody assay (IFA). It was considered positive Titers≥ 1:50. There was no significant association between location, age, gender, presence of dogs on the property, occurrence of abortion and seropositivity for N. caninum (p> 0.05). Thus, due to this high prevalence, it is suggested that this infection is common in goats in the State of Paraíba. Therefore studies about this protozoan are extremely important, seeking effective control strategies based on the assessment of risk factors.